Migration Selection, Protection, and Acculturation in Health: A Binational Perspective on Older Adults - Riosmena, Fernando (2013)
In this article, we test for four potential explanations of the Hispanic Health Paradox (HHP): the “salmon bias,” emigration selection, and sociocultural protection originating in either destination or sending country. To reduce biases related to attrition by return migration typical of most U.S.-based surveys, we combine data from the Mexican Health and Aging Study in Mexico and the U.S. National Health Interview Survey to compare self-reported diabetes, hypertension, current smoking, obesity, and self-rated health among Mexican-born men ages 50 and older according to their previous U.S. migration experience, and U.S.-born Mexican Americans and non-Hispanic whites. We also use height, a measure of health during childhood, to bolster some of our tests. We find an immigrant advantage relative to non-Hispanic whites in hypertension and, to a lesser extent, obesity. We find evidence consistent with emigration selection and the salmon bias in height, hypertension, and self-rated health among immigrants with less than 15 years of experience in the United States; we do not find conclusive evidence consistent with sociocultural protection mechanisms. Finally, we illustrate that although ignoring return migrants when testing for the HHP and its mechanisms, as well as for the association between U.S. experience and health, exaggerates these associations, they are not fully driven by return migration-related attrition.